P189 Host cell DNA methylation markers for cancer risk stratification of vulvar intraepithelial neoplasia. (1st November 2019) - Thuijs, NB; Duin, S; van Splunter, AP; Swarts, DRA; Heideman, DAM; Berkhof, J; van Beurden, M; Steenbergen, RDM; Bleeker, MCG
Abstract : Introduction/Background: High-grade vulvar intraepithelial neoplasia (VIN) is the precancerous state of vulvar squamous cell carcinoma (VSCC). Vulvar carcinogenesis is a heterogeneous disease with only a minority of VINs progressing to cancer. Because current clinical and histological classifications are insufficient to predict the cancer risk in women with VIN, affected women are treated similarly with mutilating interventions. Hence, there is a clinical need for objective biomarkers reflecting the cancer risk. In this study we assessed the potential value of DNA methylation markers for risk stratification of VIN. Methodology: A series of ∼200 vulvar tissues were assessed for methylation status including VSCC, VIN with VSCC, VIN without VSCC and normal vulvar tissue. VIN with VSCC included VIN tissue adjacent to VSCC or VIN tissue of women who developed VSCC during follow-up. VIN without VSCC was defined as VIN tissue of women who did not develop VSCC during their follow up. Multiplexed quantitative methylation-specific PCR assays were performed on twelve candidate methylation markers to analyse differential methylation. Results: Compared to normal vulvar tissue, VIN with VSCC showed increased methylation levels. These methylation levels were as high as in VSCC. Interestingly, methylation levels were found to be significantly lower in VIN without VSCC compared to VIN with VSCC or VSCC. Conclusion: Our results show that host cell DNA methylation increases with severity of vulvar disease. VIN with VSCC demonstrates a 'cancer-like' methylation pattern, reflecting the high cancer risk. Our findings indicate that host cell DNA methylation biomarkers are promising for cancer risk stratification in women with VIN. Disclosure: RDMS and DAMH have a minority stake in Self-screen BV, The Netherlands.